1994
DOI: 10.1007/bf00590957
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystocholangiography vs cystic duct cholangiography during laparoscopic cholecystectomy

Abstract: Intraoperative cholangiography performed during laparoscopic cholecystectomy provides an exact picture of the biliary anatomy. It may prevent iatrogenic bile duct injury and detect unsuspected common duct stones. Laparoscopic cannulation of the cystic duct can be difficult and time-consuming. We therefore evaluated the simpler technique of cholecystocholangiography by direct puncture and filling of the gallbladder with contrast medium. This technique was compared with cystic duct cholangiography in a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Also, CCC yielded inferior image quality and a 2.3 times longer radiation exposure. In comparative studies, Daoud et al [59] reported comparable success rates for CCC and IOC, while Glattli et al [60] found a very low success rate of 36% for CCC versus 90% in IOC. In general, success rates CCC series vary between 72 and 90% [6164].…”
Section: Resultsmentioning
confidence: 99%
“…Also, CCC yielded inferior image quality and a 2.3 times longer radiation exposure. In comparative studies, Daoud et al [59] reported comparable success rates for CCC and IOC, while Glattli et al [60] found a very low success rate of 36% for CCC versus 90% in IOC. In general, success rates CCC series vary between 72 and 90% [6164].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to catheter perforations, transection of the cystic duct, or shortness of the cystic duct, the safe closure of the cystic stump can be hampered by the IOC itself. According to Glättli et al, the technically simpler and safer means of contrasting the bile ducts by laparoscopic cholecystocholangiography yields significantly poorer results; thus, it cannot be regarded as an alternative to transcystic cholangiography [8].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,7,8,12,14 The failure rates associated with cystic duct cholangiography have been reported to range from An alternative to performing cholangiography is cholecystocholangiography, although this has been criticized for frequently yielding inadequate common bile duct opacification. [15][16][17] On the other hand, satisfactory cholangiograms using laparoscopic cholecystocholangiography have been reported in 80%-92% of patients with chronic or acute calculous cholecystitis, without any complications or false-positive findings. 4,8,10 In the present study, the biliary tree anatomy was clearly demonstrated in 90% of the 40 patients with symptomatic gallstones or chronic calculous cholecystitis.…”
Section: Discussionmentioning
confidence: 99%